Penyusunan Prosedur Tetap dan Pemasangan Rambu Evakuasi Gedung Pasar Tradisional dalam Rangka Mitigasi Bencana Gempa - Titi Kurniati; Yosritzal Yosritzal; Aner Yuweti (Warta Pengabdian Andalas, 2019)
The city of Padang needs preparedness to deal with the earthquake and tsunami, which is likely to be repeated. The places that should get more attention during a disaster are public places and public facilities, such as schools, hospitals, offices, and shopping centers. This is because the human population is quite dense in these places so that an effective and planned evacuation process is needed to avoid many casualties during a disaster. Pasar Raya Padang, located in Kampung Jao, Kecamatan Padang Barat, is the largest shopping center in the city of Padang and has a relatively dense population. West Padang is included in a high-risk zone for tsunamis, while Pasar Raya Building Block I-IV located in the Pasar Raya area of Padang does not yet have fixed procedures for dealing with disasters and evacuation guidance signs in the building whereas the existence of procedures and guidelines for evacuation is a mitigation that must be done in the context of disaster preparedness. The implementation of community service activities is focused on developing procedures to deal with the earthquake and tsunami. The results will be implemented in the form of installing evacuation signs inside the building and evacuation instructions outside the building. It is submitted planning documents for the Pasar Raya evacuation signs Block I-IV to the Padang City Regional Disaster Management Agency (BPBD). Implemented 1 signpost of assembly point and 48 evacuation guidance signs consisting of evacuation route instructions, emergency access instructions, and exit access instructions at Pasar Raya Building Block IV.